PENERAPAN MEDIA PEMBELAJARAN AR DALAM MENINGKATKAN KONSENTRASI BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS V SD - Syerina Aprilia; Mukti Sintawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the application of Augmented Reality (AR) learning media to improve student concentration in learning about ecosystems in fifth-grade elementary schools. The study used a descriptive qualitative approach, involving teachers and students as data sources. Data were collected through observation, interviews, and documentation to obtain an in-depth overview of the learning process and student responses to the use of AR. The results showed that AR media can realistically present animal objects and their habitats through 3D visualization, thereby helping students understand the abstract concept of ecosystems. The application of AR has been shown to improve several indicators of student concentration, such as increased student engagement, curiosity, learning motivation, and visual attention to the material. Students appeared more focused, actively explored AR objects, and demonstrated enthusiasm in participating in learning activities. Thus, AR can be a relevant, innovative alternative learning medium for application to other materials requiring concrete visualization.